Um olhar semiótico sobre o processo de indexação: a questão da representação e do referente - Sousa, Brisa Pozzi de [UNESP]; Almeida, Carlos Cândido de [UNESP] (My University, 2012)
The indexing process is determined the subject of the document and its relation with the representation information. To cultivate the interdisciplinary contributions is essential, especially when the relationship allows substantial additions to the area of research. Rehearse some contributions in this article of Semiotics of Charles Sanders Peirce in the field of study of the indexing process, in particular, the notions of representation and referent. It is concluded that the tripartite division of the sign provides basis for to understanding the process of thematic representation, discussing the relationship of the sign with the object and the phenomenon presented, in the indexer sees the documentary language as referent.
A semiotic look on the indexing process: The question of representation and referent
Keywords: Charles Peirce (1939-1914); Indexing Process; Information Representation; Referent; Semiotics